Fabrication and experimental study of transformer 400 V with a simple rectifier circuit design - Fitri Puspasari; Sismanto Sismanto; Ahmad Ashari (Institute of Advanced Engineering and Science, 2023)
The demand for increased voltage in renewable energy sources is relatively high. This study examines the rapid development of technology considering the use of voltage-increasing transformers. Voltage regulator circuits are generally used to stabilize the output voltage of the rectifier according to the amount of input from the transformer. However, components for high-voltage stabilizer circuits are rare, which becomes an obstacle to the stabilization of the rectifier output. This study aimed to determine the performance of the designed rectifier circuit against a non-center tap step-up direct current (DC) 400 V transformer and compare the measurement results to manual calculations. The research method is a direct comparison between the input and output voltage values of the transformer after going through a rectifier circuit. This experiment was conducted using the repeatability method three to five times for each voltage variation on the transformer. The voltage variations successfully created are 0 to 50, 0 to 100, 0 to 200, and 0 to 400 V. The output test results from the DC transformer and rectifier circuit show linear results and an increase in peak-to-peak voltage data between the transformer and rectifier outputs by 3.8%.